S44 Rct evaluation of the bronchiectasis empowerment tool self-management intervention using self-reported questionnaires and focus groups. (15th November 2017) - Brockwell, C; Wilson, AM; Clark, A; Barton, G; Pasteur, MC; Fleetcroft, R; Hill, JH; Stöckl, A
Abstract : Introduction: Evidenced self–management to guide patients in preserving their quality of life (QoL) and moderate healthcare demands, is lacking in bronchiectasis though advocated in the guidelines. 1 An expert patient plan has shown promise. 2 Aim: To measure the impact on self-efficacy (confidence in dealing with disease), of the Bronchiectasis Empowerment Tool (BET) as part of a quality of life and economic evaluation. Method: 220 people from 6 UK hospitals were randomised (computerised) to standard treatment (including BTS physiotherapy leaflet and British Lung Foundation leaflet about bronchiectasis) alone or with the addition of BET. Participants had radiological diagnosis and at least one exacerbation within 12 months of enrolment. Individuals with cystic fibrosis, traction bronchiectasis and severe uncontrolled co-morbid disease were excluded. BET, (48 pages) comprising an action-plan based on the 2010 BTS Guidelines (1) and four educational sections: sputum, health changes, medications and health interactions (with notepads), was introduced using four brief telephone calls (totalling 24 min per person). All outcomes were self-reported: The primary outcome using the Self-Efficacy Measure for Chronic Disease (SEMCD) questionnaire at 12 months. QoL measures included St George's Respiratory Questionnaire, Lung Information Needs Questionnaire (LINQ) and non-validated questionnaires. Euroqol 5 Dimension (EQ5D) and healthcare utilisation questionnaires were used for economic evaluation. Participants received questionnaires quarterly for one year. Focus groups assessed acceptability. Results: 127 participants responded at 12 months. BET did not influence SEMCD (mean difference (0.14 (95% confidence interval (95% CI −0.37 TO 0.64), p=0.59). NHS cost weren't significantly different between groups (mean difference £335.94, 95% CI £−444.97 to £1156.85) nor were Quality adjusted life years derived from EQ5D data (mean difference 0.006, 95% CI −0.042 to 0.053) or QoL. Focus group participants, diverse in severity, symptoms and isolation deemed the telephone element of BET acceptable. Conclusion: BET did not improve self-efficacy, QoL or diminish healthcare costs. Supporting literacy needs with increased contact (perhaps telephone) or novel methods of evaluation may reduce attrition in future self-management research using self-reported outcomes.